The Effect of End Milling Parameters on Surface Roughness when Machining Corrosion Resistance Alloy - M. M., Noor; K., Kadirgama; M. R. M., Rejab; M. S. M., Sani; M. M., Rahman; T. T., Mon (2009)
The increase of consumer needs for quality metal cutting related products (more precise tolerances and better product surface roughness) has driven the metal cutting industry to continuously improve quality control of metal cutting processes. Within these metal cutting processes, the end-milling process is one of the most fundamental metal removal operations used in the manufacturing industry. The aim of the this study is to develop the surface roughness prediction model for Hastelloy C-22HS with aid of statistical method, using coated carbide cutting tool under various cutting conditions. This material is superior materials for corrosion resistance which commonly used underwater applications such as submarine components and etc. This prediction model was then compared with the results obtained by experimentally. By using Response Surface Method (RSM) of experiment, first and second order models were developed with 95% confidence level. The surface roughness was developed in terms of cutting speed, feed rate and axial depth using RSM and design of experiment. In general, the results obtained from the mathematical model are in good agreement with that obtained from the experiment data’s. It was found that the feedrate, cutting speed and axial depth played a major role in determining the surface roughness. On the other hand, the surface roughness increases with a reduction in cutting speed.